Inflasi dan Imbal Hasil Saham di Bursa Efek Indonesia [Inflation and Stock Return in Indonesia Stock Exchange] - Ready Prima Dudesy; DS Priyarsono; Tony Irawan (Pusat Penelitian, Badan Keahlian DPR RI, 2018)
The performance of capital market does not only set by internal factors, but also set by external factors. One of the external factors is economic conditions. Investors can use the national economic indicator such as inflation rate for investment decisions. The purpose of this study is to identify the Indonesia’s inflation shock impact on stock returns in Indonesia Stock Exchange or IDX. The result of the study showed a causal relationship or interrelation between national inflation rate variable and stock return of basic industry and chemical sector variable. In addition the study also showed four one-way relationship of the stock return of agricultural sector which significantly affects inflation rate, the stock returns of financial sector which significantly affects inflation rate, the stock returns of composite stock index in IDX which significantly affects inflation rate, and the inflation rate which significantly affects stock returns of infrastructure sector. The Impulse of the Indonesia’s inflation rate get a negative response of the stock returns of the basic & chemical industry sectors. On the other hand, the impulse of the stock returns of the basic & chemical industry get a negative response of the Indonesia’s inflation rate. The impulse of the stock returns of agricultural sector get positive response of the national inflation rate. The impulse of stock return of financial sector get a negative response of the national inflation rate. The impulse of stock return of composite index get a negative response of the national inflation rate. The impulse of the Indonesia’s inflation rate get a negative response of the stock returns of infrastructure, public works and transportation sectors.Keywords: inflation, stock return, causalityAbstrakKinerja pasar modal tidak hanya ditentukan oleh faktor internal perusahaan saja, tetapi juga oleh faktor eksternal perusahaan. Faktor eksternal perusahaan salah satunya adalah kondisi ekonomi. Investor dapat menggunakan indikator kondisi perekonomian nasional yaitu tingkat inflasi untuk keputusan investasi. Tujuan dari penelitian ini adalah untuk mengidentifikasi pengaruh guncangan tingkat inflasi Indonesia terhadap imbal hasil saham di Bursa Efek Indonesia (BEI). Hasil penelitian menemukan satu hubungan kausalitas atau saling memengaruhi yaitu antara variabel tingkat inflasi nasional dan variabel imbal hasil saham sektor industri dasar dan kimia. Hasil penelitian juga mendeteksi bahwa terdapat empat hubungan satu arah yaitu antara imbal hasil saham sektor pertanian yang signifikan memengaruhi tingkat inflasi, imbal hasil saham sektor keuangan yang signifikan memengaruhi tingkat inflasi, imbal hasil indeks saham gabungan di BEI yang signifikan memengaruhi tingkat inflasi, dan tingkat inflasi yang signifikan memengaruhi imbal hasil saham sektor infrastruktur. Guncangan tingkat inflasi Indonesia direspon negatif oleh imbal hasil saham sektor industri dasar dan kimia. Sebaliknya guncangan imbal hasil saham sektor industri dasar dan kimia juga direspon negatif oleh tingkat inflasi nasional. Guncangan imbal hasil saham sektor pertanian direspon positif oleh tingkat inflasi nasional. Guncangan imbal hasil saham sektor keuangan direspon negatif oleh tingkat inflasi nasional. Guncangan imbal hasil indeks harga saham gabungan direspon negatif oleh tingkat inflasi nasional. Guncangan tingkat inflasi Indonesia direspon negatif oleh imbal hasil saham sektor infrastruktur, pekerjaan umum, dan transportasi.Kata kunci: inflasi, imbal hasil saham, kausalitas